A New Light on Photosystem II Maintenance in Oxygenic Photosynthesis - Liu, Jun; Lu, Yan; Hua, Wei; Last, Robert L. (Frontiers in Plant Science, 2019)
Life on earth is sustained by oxygenic photosynthesis, a process that converts solar energy, carbon dioxide and water into chemical energy and biomass. Sunlight is essential for growth and productivity of photosynthetic organisms. However, exposure to an excessive amount of light adversely affects fitness due to photooxidative damage to the photosynthetic machinery, primarily to the reaction center of the oxygen-evolving photosystem II (PSII). Photosynthetic organisms have evolved diverse photoprotective and adaptive strategies to avoid, alleviate, and repair PSII damage caused by high-irradiance or fluctuating light. Rapid and harmless dissipation of excess absorbed light within antenna as heat, which is measured by chlorophyll fluorescence as non-photochemical quenching (NPQ), constitutes one of the most efficient protective strategies. In parallel, an elaborate repair system represents another efficient strategy to maintain PSII reaction centers in active states. This article reviews both the reaction center-based strategy for robust repair of photodamaged PSII and the antenna-based strategy for swift control of PSII light-harvesting (NPQ). We discuss evolutionarily and mechanistically diverse strategies used by photosynthetic organisms to maintain PSII function for growth and productivity under static high-irradiance light or fluctuating light environments. Knowledge of mechanisms underlying PSII maintenance would facilitate bioengineering photosynthesis to enhance agricultural productivity and sustainability to feed a growing world population amidst climate change.